Depression, Anxiety and Stress among Nursing Students at Biratnagar - Sita Chapagain; Saraswata Neupane; Indira Pokhrel; Tara Kumari Kafle (Journal of Nobel Medical College, 2023)
Background: Nursing students’ depression, anxiety and stress are important issue in society with strongest connection to client recover when these students become nurse in future.Such psychological distress among them leads to less productivity, reduced quality of life, learning difficulties and may negatively affect patient care.